Strategi Pengisian Baterai pada Sistem Panel Surya Standalone Berbasis Kontrol PI Multi-Loop - Hidayat, Khusnul; Hasani, Mohammad Chasrun; Mardiyah, Nur Alif; Effendy, Machmud (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2021)
This study discusses the power control strategy in a standalone photovoltaic-battery hybrid system. The life-time of the battery will be shorter if the battery is often charged with high current and exceeds its State-of-Charge (SoC). Therefore, a control method is needed to control the power flow on the DC bus and the charging current as well as the SoC of the battery so that the battery has a long life-time. The proposed system uses two dc-dc converters to connect photovoltaic (PV) and lead-acid batteries to the load. The unidirectional DC-DC converter is used as the interface between the PV and the DC bus, the bidirectional DC-DC converter is used as the interface between the battery and the DC bus. The control strategy plays a role in controlling the power flow between the converter and the load to maintain the balance of power in the system and controlling the battery to support PV when the available PV power is not enough to meet the load. The multi-loop control strategy is proposed in this study, one of the loops is used to maintain the SoC of the battery in order to control the PV output power to avoid over-charging. Another loop is used to ensure the balance of the system's power when the battery is charging at its maximum charge current. The proposed control system is implemented without requiring any conditions for the control to operate. The simulation results show that the proposed multi-loop control can control the power flow in the system while maintaining the maximum charging current and battery SoC limits.